Anti-inflammatory activity of essential oils from three species of Lamiaceae: a literature review (Revista Brasileira de Plantas Medicinais, 2020)
Essential oils (EOs) are highly volatile, strong-smelling complex compounds that are extracted from aromatic plants and have about a dozen to several hundred components. The majority of these include terpenes (oxygenated or not), such as monoterpenes and largely sesquiterpenes in addition to phenols and phenylpropanoids. This ample composition gives it several actions such as antioxidant, antiseptic, bactericidal, fungicidal, among others. The objective of this work was to describe the anti-inflammatory properties of EO of three species of Lamiaceae (Rosmarinus officinalis, Origanum vulgare and Thymus vulgaris) found in the literature in the last ten years; and to compare the main constituents with their anti-inflammatory mechanisms of action. For this, a literature review was carried out using the keywords "anti-inflammatory", "essential oil", and the scientific names of the species including their english correlates in the databases - PubMed, Science Direct and Scielo. We excluded the articles of revision and those published prior to 2007. We conclude the diversified constitution of the assets in the EO in the same species or between different entailing in differentiated anti-inflammatory mechanisms. It was noticed that the EOs from R. officinalis presented 1.8 cineole, and both EOs from O. vulgare and T. vulgaris, carvacrol, as main constituents contributing to various anti-inflammatory mechanisms. The main mechanisms verified in the investigation were evidenced in experimental models, in vivo, by the reduction of edema in the paw of rats related to the inhibition of the release of prostaglandins with the administration of the EO of R. officinalis, in vivo in animals and in vitro in humans, by inhibition of the release of pro-inflammatory cytokines with the use of OE of O. vulgare acting on intestinal and dermal inflammation and, in vitro and in vivo in animals, for the effects on colitis, edema and endothelial inflammation with the use of OE of T. vulgaris by inhibiting genes related to interleukin production, COX-2 expression and leukocyte migration. This may enhance the use of EO as viable and natural alternatives to the conventional treatment of inflammation by avoiding or ameliorating side effects. However, further investigations are still needed to clarify the mechanisms of anti-inflammatory action of its isolated constituents as well as their possible toxic effects.